RETAIL INVESTORS’ PERCPTION ON FINANCIAL DERIVATIVES IN INDIA - Pasha, Shaik Abdul Majeeb (European Scientific Journal, ESJ, 2013)
The Indian financial market has undergone paradigm changes during last two decades. One of the most significant changes is the introduction of derivatives during the year 2000 based on recommendation of expert committees to provide the facility for hedging in the most cost-efficient way against market risk. Though the Indian capital market size is wider around Rs.20,000,000 crores p.a. both in NSE and BSE even after 12 years, from introduction of derivatives, market participants especially small–retail individual investors are not familiar with the concept of derivatives. Still they have misconceptions about derivatives. They believe in the myths of derivatives instead of realities. Indeed, they feared derivatives due to lack of knowledge about them and their use. An attempt is made by the researcher to know what kind of perceptions had by retail investors in India based on Andhra Pradesh State reference with a sample size of 500 respondents by using simple percentage bar diagrams.. Ultimately, financial derivatives should be considered part of any investor’s risk– management strategy to ensure that value – enhancing investment opportunities are pursued.